8-Styryl-substituted coralyne derivatives as DNA binding fluorescent probes. Issue 18 (8th February 2017) - Pithan, P. M.; Decker, D.; Druzhinin, S. I.; Ihmels, H.; Schönherr, H.; Voß, Y.
Abstract : 8-Styryl-substituted coralyne derivatives bind to duplex and quadruplex DNA and may be used for fluorimetric staining of nucleoli in cells. Abstract : Six new 8-styryl-substituted coralyne derivatives4a–f were synthesized from coralyne (2 ) by a base catalysed Knoevenagel type reaction. It was shown by photometric and fluorimetric titrations of double stranded and quadruplex DNA to4b–d as well as by fluorimetric DNA denaturation experiments that these ligands bind to DNA with different binding modes at varying ligand-DNA ratios (LDR). Specifically, the addition of DNA caused initially a hypochromic effect in absorbance and, at a particular LDR, the development of a new red shifted absorption band with a hyperchromic effect. Furthermore, 4b–d induced a significant and selective stabilization of quadruplex DNA towards unfolding (Δ T m = 31.6–32.9 °C at LDR = 5), which is even more pronounced as compared to the parent compound coralyne (2 ). Most notably, the addition of DNA to the dimethylamino-substituted derivative4b leads to a new, strongly red-shifted emission band at 695 nm. Hence, this derivative is a fluorescent probe that changes its fluorescence colour from green to red in the presence of DNA and even allows the fluorimetric analysis of living cells by staining of the nucleoli.